Investigation of the interactions between proton exchange membrane fuel cell and interleaved DC/DC boost converter in case of power switch faults. (5th January 2015) - Guilbert, Damien; Gaillard, Arnaud; Mohammadi, Ali; N'Diaye, Abdoul; Djerdir, Abdesslem
Abstract: In recent years, the impact of the current ripple on Fuel Cell (FC) performances, particularly on its lifetime has gained a growing interest from the international scientific community. Polymer Electrolyte Membrane Fuel Cells (PEMFC) usually require a DC/DC boost converter to increase the output FC voltage. The output FC current is then submitted to the high switching frequency (i.e. >10 kHz) leading to a current ripple. Generally, in order to study the impact of the current ripple on FC performances, current ripple coming from DC/DC converters is simulated by means of an electronic load and signal generator. However, the use of a signal generator limits the scope of investigation up to a frequency of the current ripple equal to 10 kHz and by considering a healthy operation mode of the converter. For this reason, several aspects of the interaction between FC and DC/DC converter (operating at more than 10 kHz) require further investigation for automotive applications where the switching frequency is increased in order to reduce the volume of the converter, particularly in case of a faulty operation mode when power switch fault occurs from the DC/DC converter. The purpose of this paper is to provide simulation and experimental results at a switching frequency equal to 20 kHz, regarding the impact of open circuit fault of a power switch on the FC behavior, efficiency, H2 consumption, reliability and performance. Highlights: Review concerning the high-frequency current ripple on fuel cell. Brief review of considered faults in DC/DC converter. Impact of power switch fault on the fuel cell performances. Impact of power switch fault on the DC/DC converter operation. We summarize and discuss the impact of faulty operating mode on the fuel cell.